2019
DOI: 10.3399/bjgp19x704609
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and emergency department visits by a homeless population: a database study in specialist general practice

Abstract: BackgroundEstimating healthcare needs of the homeless is associated with challenges in identifying the eligible population.AimTo explore the demographic characteristics, disease prevalence, multimorbidity, and emergency department visits of the homeless population.Design and settingEMIS electronic database of patient medical records and Quality and Outcomes Framework (QOF) data of all 928 patients registered with a major specialist homeless primary healthcare centre based in the West Midlands in England, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 49 publications
5
69
2
Order By: Relevance
“…Participants in these public involvement sessions said that they would trust pharmacists to prescribe medicines to them. Cardiovascular diseases, mental health and substance misuse issues are often undiagnosed and under-treated [6,10,11], and pharmacists have the potential to address these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in these public involvement sessions said that they would trust pharmacists to prescribe medicines to them. Cardiovascular diseases, mental health and substance misuse issues are often undiagnosed and under-treated [6,10,11], and pharmacists have the potential to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…They die at an average age of 43 to 45 years [5]. A recent study conducted with over 900 homeless people in England showed a high prevalence of severe mental health problems, alcohol dependence, substance misuse and infectious hepatitis C [6]. A study in Scotland showed that the extent of multi-morbidity in homeless population, with a mean age of 40 years, was comparable to persons over 85 years in the general population [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study suggest that promotion of self-care among Poor mental health, including the experience of stigma and discrimination was a recurrent theme in the data. Poor mental health can often be the cause and consequences of homelessness (Bowen et al, 2019). Various barriers to people's access to mental health services have been described in the literature with concurrent substance misuse and history of self-harm often excluding patients access to mental health services (Gunner et al, 2019).…”
Section: Pr Ac Ti Ce and Re S E Arch Implic Ationsmentioning
confidence: 99%
“…10,11 Mental illness, pain and addictions may be poorly managed 12 with evidence suggesting under prescribing and low rates of prescription adherence 13,14 Patterns and reasons for emergency healthcare utilisation differ between people experiencing homelessness and those who are housed: ED visits, hospitalisations and readmissions are higher. 15,16 Availability and uptake of preventative healthcare is lower 9,16,17 and presentations to Family (General) Practitioners tend to be reactive. 18 Almost one third of homeless deaths are preventable by timely and effective use of health services 6 yet there is a lack of community based effective and cost effective complex interventions by healthcare professionals, proven to increase anticipatory care and reducing unscheduled care.…”
Section: Introductionmentioning
confidence: 99%